Effects of nonlinear frequency compression on speech identification in children with hearing loss - Hillock-Dunn, Andrea (Ear Hear, 2014)
OBJECTIVE: This study evaluated effects of nonlinear frequency compression (NLFC) processing in children with hearing loss for consonant identification in quiet and for spondee identification in competing noise or speech. It was predicted that participants would benefit from NLFC for consonant identification in quiet when access to high-frequency information was critical, but that NLFC would be less beneficial, or even detrimental, when identification relied on mid-frequency cues. Further, it was hypothesized that NLFC could result in greater susceptibility to masking in the spondee task. The rationale for these predictions is that improved access to high-frequency information comes at the cost of decreased spectral resolution. DESIGN: A repeated-measures design compared speech perception outcomes in 17 pediatric hearing aid users (9-17 years) wearing Naida V SP “laboratory” hearing aids with NLFC on and off. Data were also collected in an initial baseline session in which children wore their personal hearing aids. Children with a wide range of audiometric configurations were included, but all participants were full-time users of hearing aids with active NLFC. For each hearing aid condition, speech perception was assessed in the sound field using a closed-set 12-alternative consonant-vowel identification measure in quiet, and a closed-set 4-alternative spondee identification measure in a speech-shaped noise or in a two-talker speech masker. RESULTS: No significant differences in performance were observed between laboratory hearing aid conditions with NLFC activated or deactivated for either speech perception measure. An unexpected finding was that the majority of participants had no difficulty identifying the high-frequency consonant /s/, even when NLFC was deactivated. Investigation into individual differences revealed that subjects with a greater difference in audible bandwidth with NLFC on versus NLFC off were less likely to demonstrate improvements in high-frequency consonant identification in quiet, but were more likely to demonstrate improvements in spondee identification in speech-shaped noise. Group results observed in the initial baseline assessment using personal aids fitted with more aggressive NLFC settings than used in laboratory aids indicated better consonant identification accuracy in quiet. However spondee identification in the two-talker masker was poorer with personal compared with laboratory hearing aids. Comparisons across personal and laboratory hearing aids are tempered, however, by the potential of an order effect. CONCLUSIONS: The observation of comparable performance with NLFC on and off in the laboratory aids provides evidence that NLFC is neither detrimental nor advantageous when modest in strength. Results with personal hearing aids fitted with stronger compression settings than laboratory aids (NLFC on) highlight the critical need for further research to determine the impact of NLFC processing on speech perception for a wider range of speech perception measures and compression settings.